Molecular insight in intrarenal inflammation affecting four main types of cells in nephrons in IgA nephropathy - Zhang, Haidong; Deng, Zhenling; Wang, Yue (Frontiers in Medicine, 2023)
Immunoglobulin A nephropathy (IgAN) is the most common primary glomerulonephritis and the leading cause of kidney failure in the world. The current widely accepted framework for its pathogenesis is the “multi-hit hypothesis.” In this review, we mainly discussed the intrarenal inflammation in IgAN, which is initiated by immune complex deposition with complement molecule activation, by focusing on four main types of cells in nephrons including mesangial cells, endothelial cells, podocytes, and tubular epithelial cells (TECs). Galactose-deficient IgA1 (Gd-IgA1)-containing immune complexes deposit in the mesangium and activate complement molecules and mesangial cells. Activation of mesangial cells by Gd-IgA1 deposition with enhanced cellular proliferation, extracellular matrix (ECM) expansion, and inflammatory response plays a central role in the pathogenesis of IgAN. Regional immune complex deposition and mesangial–endothelial crosstalk result in hyperpermeability of endothelium with loss of endothelial cells and infiltration barrier proteins, and recruitment of inflammatory cells. Podocyte damage is mainly derived from mesangial–podocyte crosstalk, in which tumor necrosis factor-α (TNF-α), transforming growth factor-β (TGF-β), renin-angiotensin-aldosterone system (RAAS), and micro-RNAs are the major players in podocyte apoptosis and disorganization of slit diaphragm (SD) related to proteinuria in patients with IgAN. In addition to filtrated proteins into tubulointerstitium and mesangial–tubular crosstalk involved in the injury of TECs, retinoic acid has been discovered innovatively participating in TEC injury.